Final Draft PAME Work Plan 2009-2011. - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment (PAME), 2009)
The PAME working group is the Arctic Council body that addresses policy and non- emergency pollution prevention and control measures related to the protection of the Arctic marine and coastal environment from land and sea-based activities influencing the state of the central Arctic Ocean and its marginal seas. The PAME Work Plan 2009 – 2011 was developed according to its mandate and priorities of the Arctic Council Chairmanship. This Work Plan is based on three objectives followed by a set of specific actions which in some instances represent a continuation of ongoing activities. The aim is to respond to emerging issues in line with the priorities of the Arctic Council Chairmanship and further advance the implementation of specific strategic actions of the Arctic Marine Strategic Plan (2004) that outlines the overall direction of the Arctic Council for the protection of the Arctic marine environment.